Metal-Doped HZSM-5 Zeolite Catalysts for Catalytic Cracking of Raw Bio-Oil: Exploring Activity toward Value-Added Products - Chiosso, María Eugenia (2023)
Catalytic cracking of bio-oil, conducted at atmospheric pressure without hydrogen supply, is a cost-effective and versatile approach for the targeted synthesis of biofuels and platform chemicals. The conversion of raw bio-oil follows intricate reaction pathways strongly influenced by the catalyst properties. In this work, we explore the use of various transition metals (Cr, Fe, and Zn) to modify the properties of HZSM-5 zeolite and assess their impact on the catalytic cracking of real raw bio-oil feedstock. The effect of metal loading on physical and chemical characteristics of metal-doped zeolite catalysts was studied through XRD, XRF, N2 physisorption, NH3-TPD, FTIR, H2-TPR. The behavior of each catalyst was evaluated in a continuous two-step catalytic cracking system (TS-CC) operating at 450 °C and space-time 0.7 gcatalysth/gfeed. The results highlight the importance of carefully selecting active metal species to optimize the performance of HZSM-5 in the catalytic cracking of bio-oil. Cr and Fe were found to be effective metals in increasing the selectivity of C2–C4 olefins in the gas product and mono-aromatics in the hydrocarbon liquid product, whereas the Zn-doped catalyst exhibits poor activity compared to bulk zeolite. Furthermore, a significant impact of the metal oxidation state on catalytic activity was observed, with reduced metals promoting the formation of H2, CO, and CO2 at the expense of hydrocarbon production.